Development and quality of pineapple guava fruit in two locations with different altitudes in Cundinamarca, Colombia - Parra-Coronado,Alfonso (2015)
Fruit growth is stimulated by different weather conditions. The aim of this study was to determine the influence of weather conditions on the physicochemical properties of pineapple guava fruit growth. Twenty trees were marked in two production areas located at different altitudes (1,800 and 2,580 m.a.s.l.), and measurements were performed every 7 days from 99 and 141 days post-anthesis to harvest at altitudes of 1,800 and 2,580 m.a.s.l., respectively. The results indicate that altitude and weather conditions greatly influence the growth and development of pineapple guava fruit, and these effects are primarily manifested in the physical characteristics of the fruit. The weight and size of the fruit at harvest are directly related to the altitude of the production area. The weather condition that has the greatest impact on total titratable acidity at harvest is cumulative radiation during fruit growth; the highest value of total soluble solids at harvest corresponds to the location with the higher altitude, lower rainfall and relative humidity and higher cumulative radiation during the fruit growth period. The hue angle and pulp firmness at harvest are not influenced by the location or weather conditions at any location and do not determine the fruit quality at harvest time.